Discrete element modelling of cone penetration testing in granular materials - Falagush, Omar (2014)
Cone penetration testing (CPT) is one of the most versatile devices for in situ soil testing. With minimal disturbance to the ground, it provides information about soil classification and geotechnical parameters. Several researchers have used different numerical techniques such as strain path methods and finite element methods to study CPT problems. The Discrete Element Method (DEM) is a useful alternative tool for studying cone penetration problems because of its ability to provide micro mechanical insight into the behaviour of granular materials and cone penetration resistance.